Implementation Of The Blended Learning Model In Class VIIIA Social Studies Subjects At Air Hitam 1 Public Middle School, West Lampung Regency - Ardila, Evi; Utami, Dian; Pargito, Pargito (FKIP Universitas Lampung, 2023)
This study aims to determine how to implement the blended learning model in social studies learning for class VIIIA SMPN 1 Air Hitam. Blended learning is learning that is best used when transitioning to a normal state, this learning combines offline learning with online learning. The research method used a qualitative approach and this research was conducted at SMPN 1 Air Hitam. Data collection techniques with interviews, observation and documentation. The sampling technique used purposive sampling aimed at school principals, social studies teachers and SMPN 1 Air Hitam students. Test the validity of the data with technical triangulation and data analysis with interaction analysis whose steps start from data collection, data reduction, data presentation and verification. The results of the research on the implementation of the blended learning learning model have been carried out, starting from lesson planning, implementing learning according to the blended learning syntax, namely searching of information, acquisition of information and synthesizing of knowledge which is carried out both in online and offline learning. Assessment of blended learning includes assessment of attitudes, knowledge and skills. The conclusion of this study is that the implementation of the blended learning model in class VIII A can be seen through the planning activities that the teacher has prepared learning tools, schedules and teaching materials. The implementation activities are in accordance with the blended learning syntax. Judgment activities are carried out offline and online.Keywords: Blended learning, Implementation, Social Studies SubjectsDOI: http://dx.doi.org/10.23960/E3J/v6i1.118-125